Investment strategy on indonesia islamic stocks using Greenblatt Magic Formula - Setiawan, Alfianto Hendry; Fitri, Resfa; Muthohharoh, Marhamah; Irfany, Mohammad Iqbal (Goodwood Publishing, 2023)
Purpose: This study analyzes the portfolio form based on the Magic Formula investment strategy introduced by Greenblatt (2006). Research methodology: The portfolio formed is evaluated using the Sharpe, Treynor, and Jensen indices. Results: The results show that the Magic Formula investment portfolio provides higher returns than the reference index from June 2018 to May 2021, specifically -1.45% compared to -3.26%. The performance evaluation value of the Magic Formula investment portfolio was better than that of the reference index. Limitations: Although the Magic Formula portfolio performs well during the study period, investment portfolios can also be built and evaluated using other portfolio formulas. Contribution: This evidence shows that the Greenblatt Magic Formula investment strategy performs well because it can provide a greater return with less risk.